2017
DOI: 10.1108/bepam-12-2016-0086
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and cost critical elements: a comparative analysis of two office buildings

Abstract: Purpose The purpose of this paper is to identify and compare cost and carbon critical elements of two office buildings, and to help achieve an optimum balance between the capital cost (CC) and embodied carbon (EC) of buildings. Design/methodology/approach Case study approach was employed to study cost and carbon critical elements of two office buildings as it allows an in-depth and holistic investigation. Elemental estimates of CC and EC were prepared from BoQs of the two buildings by obtaining rates from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
(33 reference statements)
0
10
0
1
Order By: Relevance
“…Identification of hotspots is crucial to reduce EC impacts of building designs right from the early stages of the design process. However, the knowledge about carbon hotspots is still developing (see, Victoria and Perera, 2018; Victoria et al , 2017). Carbon hotspots may vary from one building to another depending on the function of the building (Ashworth and Perera, 2015; Perera and Victoria, 2017) due to differing element intensities.…”
Section: Carbon Hotspots Of Buildingsmentioning
confidence: 99%
“…Identification of hotspots is crucial to reduce EC impacts of building designs right from the early stages of the design process. However, the knowledge about carbon hotspots is still developing (see, Victoria and Perera, 2018; Victoria et al , 2017). Carbon hotspots may vary from one building to another depending on the function of the building (Ashworth and Perera, 2015; Perera and Victoria, 2017) due to differing element intensities.…”
Section: Carbon Hotspots Of Buildingsmentioning
confidence: 99%
“…IP-4, IP-6 and IP-7 expressed the need to consider material and design optimization in developing structural designs to ensure the minimization of ineffective material utilization and material wastage. The findings of Victoria et al (2017) and Victoria and Perera (2018) support this view, where they have identified structural elements of a building, specifically the building frame and substructure to be embodied carbon (EC) and cost critical elements, which offer greater potential for EC management during building design. IP-7 further stated that the general tendency among structural engineers to overdesign structural components as a contingency measure also needs to be reduced, as much as possible, since it reflects on wasted resource allocations.…”
Section: Role Of Architects In Ensuring Energy Efficiency Through Building Designmentioning
confidence: 79%
“…Their results revealed that there is a strong relationship between EC and cost. Similarly, studies carried out by Victoria et al (2017), Jiao et al (2012), Copiello (2016) in the United Kingdom, China and Italy, respectively, revealed the existence of carbon-cost relationship in certain building elements or materials. Similarly, it is important to explore the possibility of a cost-carbon relationship in school buildings of Australia.…”
Section: Introductionmentioning
confidence: 86%